The Homotopy Perturbation Renormalization Group Method to Solve the WKB Problem with Turn Points (Communications in Mathematical Research, 2019)
In this paper, we give the homotopy perturbation renormalization groupmethod, this is a new method for turning point problem. Using this method, the independent variables are introduced by transformation without introducing new relatedvariables and no matching is needed. The WKB approximation method problem canbe solved.
Keywords: homotopy movement; renormalization group method; turn point WKB problem.